Technology use as a support tool by secondary students with autism. (January 2018) - Hedges, Susan H; Odom, Samuel L; Hume, Kara; Sam, Ann
The purpose of this study was to examine how secondary students with autism spectrum disorder use technology in supportive ways. In this self-report survey study, 472 adolescents with autism spectrum disorder enrolled in high school described the forms of technology they use and purposes for which they use it. Students reported the benefits as well as barriers to technology use at school. They reported using technology in school and home settings in a variety of supportive ways such as increasing their independence, reducing their anxiety, and increasing their social opportunities. Findings suggest that practitioners may benefit from learning how to integrate technology as an instructional and support tool for their students with autism spectrum disorder. Recommendations for future research are provided.